2019
DOI: 10.1136/heartjnl-2019-314878
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the association of risk factors for heart failure incidence and mortality

Abstract: BackgroundThere are known risk factors associated with the development of heart failure (HF), but it is not fully understood whether these differ by sex.ObjectivesTo investigate sex differences in risk factors for HF incidence and mortality.Methods468 941 participants (55.9% women, age range 37–73 years) were included. Established CVD risk factors (hypertension, hypercholesterolaemia, diabetes type 1 and 2, adiposity, smoking, physical activity and poor diet) and novel risk factors (grip strength, fitness, TV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 27 publications
2
34
0
Order By: Relevance
“…Previous research has shown that there are differences in the onset and impact of cardiovascular disease and HF according to gender [ 18 , 19 , 20 , 21 ]. Male gender is an independent cardiovascular risk factor and determines that cardiovascular disease develops at a younger age.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that there are differences in the onset and impact of cardiovascular disease and HF according to gender [ 18 , 19 , 20 , 21 ]. Male gender is an independent cardiovascular risk factor and determines that cardiovascular disease develops at a younger age.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between gender and heart failure is much stronger in women than in men. This correlation leads to increased heart failure and, therefore, more digoxin use in women (13). The fact that valve diseases and rhythm disorders are more common in women (14) and that mortality occurs at a later age compared to men may cause digoxin use to appear relatively higher in women.…”
Section: Discussionmentioning
confidence: 99%
“…The University of Glasgow has expertise on vascular neurological and cardiometabolic diseases [28][29][30]. The primary source of data is the UK Biobank, which recruited 502,536 participants, aged 39-72 years, from the general population between 2007 and 2010.…”
Section: University Of Glasgow Ukmentioning
confidence: 99%